Faktor – Faktor yang Mempengaruhi Sikap Remaja terhadap Hubungan Seksual Pranikah pada Siswa SMA Negeri 46 Jakarta - Hendrawati Hendrawati; Yusnita Yusnita (STIKes Persada Husada Indonesia, 2014)
Knowledge about reproductive health for adolescents and the role of parents and peers in providing information about is adolescent sexual and reproductive health are quite essential, the mass media in the form of books and porn movies are a viable alternative for teenagers to obtain information about reproductive health and may influences adolescent behaviors to support premarital sexual relations with a partner as an expression of affection. Although they have studied biology which include reproductive health lesson and religious instruction at each level of school education, but it does not guarantee high school students (adolescents) not to have premarital sexual behavior. This study aims to determine factors that influence adolescent attitudes toward premarital sexual relations at SMA Negeri 46 Jakarta in 2011. Qualitative research methods were used with cross-sectional design and samples of 156 people. Factors that influence the behavior of premarital sexual relationships in SMA Negeri 46 knowledge with the p value of 0.000, emotional intelligence with a p value of 0.126, Peer pressure with p value of 0.467, the mass media with the p value of 0.000, and understanding of religion with p value of 0.001. From the five research variables, three variables have a significant relationship with premarital sexual behavior. Results from multiple linear regression analysis shows there are four variables that influence to the premarital sexual behavior which are knowledge, mass media, understanding of religion, and emotional intelligence. Recommended SMA 46 to increase sexual reproduction education through mass media as well as understanding of the religion in order to improve emotional intellige that can prevent adolescent premarital sexual behavior.